Identification of microbially induced sedimentary structures over a tidal flat - Cuadrado, Diana Graciela (2007)
The influence of microbial activity in carbonatic environments leading to stromatolite build-ups is widely known. In siliciclastic environments, however, this influence has been far less studied. The present study was carried out in this type of environment and determined the importance of cyanobacterias in the preservation of sedimentary structures. Similar sedimentary structures were also recognized in the rock record by other studies. Therefore, if we know the environment of formation and conservation of such structures, then the paleoenvironment of the rock could be inferred. In the tidal flats of the Bahía Blanca Estuary, microbial mats were identified. Their interaction with sediments, lead to a stabilized flat by shielding from erosion the existing sedimentary structures. Since it is the first time these structures are mentioned in a present-day environment in Argentina, a detailed description of the bio-sedimentological interaction is presented and our results compared with others from different climatic zones, namely, temperate humid and subtropical arid. Finally the occurrence of zeolites, an authigenic mineral, indicated that the sediment would be in the early stages of diagenesis.